Fracture Incidence in Adult Kidney Transplant Recipients. Issue 1 (January 2016) - Naylor, Kyla L.; Jamal, Sophie A.; Zou, Guangyong; McArthur, Eric; Lam, Ngan N.; Leslie, William D.; Hodsman, Anthony B.; Kim, S. Joseph; Knoll, Gregory A.; Fraser, Lisa-Ann; Adachi, Jonathan D.; Garg, Amit X.
Abstract : Background: It remains uncertain whether kidney transplant recipients are a high-risk group for fracture. Methods: We conducted a cohort study using Ontario, Canada health care databases to estimate the 3-, 5- and 10-year cumulative incidence of nonvertebral fracture (proximal humerus, forearm, hip) in adult kidney transplant recipients between 1994 and 2009, stratifying by sex and age (<50 versus ≥50 years) at transplant. We also assessed the 3-year cumulative incidence of all fracture locations (excluding skull, toes, and fingers) and falls, 10-year cumulative incidence of hip fracture alone, and nonvertebral fracture incidence in recipients compared to nontransplant reference groups matched on age, sex, and cohort entry year. We studied 4821 recipients (median age, 50 years). Results: Among the age and sex strata, female recipients aged 50 years or older had the highest 3-year cumulative incidence of nonvertebral fracture (3.1%; 95% confidence interval [95% CI], 2.1-4.4%). Recipients had a higher 3-year cumulative incidence of nonvertebral fracture (1.6%; 95% CI, 1.3-2.0%) compared to the general population with no previous nonvertebral fracture (0.5%; 95% CI, 0.4-0.6%; P < 0.0001) and nondialysis chronic kidney disease (1.1%; 95% CI, 0.9-1.2%; P = 0.03), but a lower fracture incidence than the general population with a previous nonvertebral fracture (2.3%; 95% CI, 1.9-2.8%; P = 0.007). The 10-year cumulative incidence of hip fracture in all recipients was 1.7% (≥3% defined as high risk in clinical guidelines). Conclusions: Kidney transplant recipients may have a lower fracture risk than previously suggested in the literature. Results inform our understanding of fracture incidence after kidney transplantation and how it compares to nontransplant populations. Abstract : An analysis of 4821 kidney transplant recipients with median age of 50 years in the Ontario, Canada healthcare databases of kidney transplant patients transplanted between 1994–2009 shows that cumulative non-vertebral fracture rates are lower than previously reported. Supplemental digital content is available in the text.